La planeación estratégica como herramienta para incrementar la productividad y sostenibilidad de las empresas. Caso: grandes empresas del sector de servicios de aseo y mantenimiento de instalaciones en Bogotá (2020)
This work seeks to analyze the aspects of strategic planning as a tool to increase the sustainability of companies in the sector of provision of cleaning and maintenance services in the city of Bogotá, using as a case study two of the largest companies in that sector. The work begins with the identification of the processes of design, implementation and monitoring of strategic planning in companies in the cleaning and maintenance services sector of the City of Bogotá. For this, case studies found within the review process are initially presented in 10 Universities classified by the Model of Educational Performance Indicators - MIDE. Subsequently, the context of the companies that are part of the case study of this work is shown and, finally, the management models of the case study companies are detailed based on the design, implementation and monitoring processes.